Germline variation in ADAMTSL1 is associated with prognosis following breast cancer treatment in young women. Issue 1 (December 2017) - Kadalayil, Latha; Khan, Sofia; Nevanlinna, Heli; Fasching, Peter; Couch, Fergus; Hopper, John; Liu, Jianjun; Maishman, Tom; Durcan, Lorraine; Gerty, Sue; Blomqvist, Carl; Rack, Brigitte; et al.
Abstract To identify genetic variants associated with breast cancer prognosis we conduct a meta-analysis of overall survival (OS) and disease-free survival (DFS) in 6042 patients from four cohorts. In young women, breast cancer is characterized by a higher incidence of adverse pathological features, unique gene expression profiles and worse survival, which may relate to germline variation. To explore this hypothesis, we also perform survival analysis in 2315 patients aged ≤ 40 years at diagnosis. Here, we identify two SNPs associated with early-onset DFS, rs715212 (P meta  = 3.54 × 10−5 ) and rs10963755 (P meta  = 3.91 × 10−4 ) inADAMTSL1 . The effect of these SNPs is independent of classical prognostic factors and there is no heterogeneity between cohorts. Most importantly, the association with rs715212 is noteworthy (FPRP <0.2) and approaches genome-wide significance in multivariable analysis (P multivariable  = 5.37 × 10−8 ). Expression quantitative trait analysis provides tentative evidence that rs715212 may influenceAREG expression (P eQTL  = 0.035), although further functional studies are needed to confirm this association and determine a mechanism. Genetic variance can influence breast cancer prognosis. Here, the authors conduct a meta-analysis to explore genetic variance linked to breast cancer in young women, identifying a prognostic association with germline variation of ADAMTSL1.